Corpse decomposition increases the diversity and abundance of antibiotic resistance genes in different soil types in a fish model. (1st October 2021) - Feng, Tianshu; Su, Wanghong; Zhu, Jianxiao; Yang, Jiawei; Wang, Yijie; Zhou, Rui; Yu, Qiaoling; Li, Huan
Abstract: As a common natural phenomenon, corpse decomposition may lead to serious environmental pollution such as nitrogen pollution. However, less is known about antibiotic resistance genes (ARGs), an emerging contaminant, during corpse degradation. Here, ARGs and microbiome in three soil types (black, red and yellow soil) have been investigated between experimental and control groups based on next-generation sequencing and high-throughput quantitative PCR techniques. We found that the absolute abundance of total ARGs and mobile genetic elements (MGEs) in the experimental groups were respectively enriched 536.96 and 240.60 times in different soil types, and the number of ARGs in experimental groups was 7–25 more than that in control groups. For experimental groups, the distribution of ARGs was distinct in different soil types, but sulfonamide resistance genes were always enriched. Corpse decomposition was a primary determinant for ARGs profiles. Microbiome, NH4 + concentrates and pH also significantly affected ARGs profiles. Nevertheless, soil types had few effects on ARGs. For soil microbiome, some genera were elevated in experimental groups such as the Ignatzschineria and Myroides . The alpha diversity is decreased in experimental groups and microbial community structures are different between treatments. Additionally, the Escherichia and Neisseria were potential pathogens elevated in experimental groups. Network analysis indicated that most of ARGs like sulfonamide and multidrug resistance genes presented strong positively correlations with NH4 + concentrates and pH, and some genera like Ignatzschineria and Dysgonomonas were positively correlated with several ARGs such as aminoglycoside and sulfonamide resistance genes. Our study reveals a law of ARGs' enrichment markedly during corpse decomposing in different soil types, and these ARGs contaminant maintaining in environment may pose a potential threat to environmental safety and human health. Graphical abstract: Image 1 Highlights: Corpse decomposition changes soil environment. Corpse decomposition causes the accumulation of ARGs in all soil types. Soil types have few impact on ARGs. Treatment, microbiome, NH4 + concentrates and pH are primary determinants. ARGs are correlated with integrons, NH4 +, pH and microbes during corpse decay.